2020
DOI: 10.3389/fpubh.2020.605149
|View full text |Cite
|
Sign up to set email alerts
|

Lost in Transition: Health Care Experiences of Adults Born Very Preterm—A Qualitative Approach

Abstract: Introduction: Adults Born Very Preterm (ABP) are an underperceived but steadily increasing patient population. It has been shown that they face multiple physical, mental and emotional health problems as they age. Very little is known about their specific health care needs beyond childhood and adolescence. This article focuses on their personal perspectives: it explores how they feel embedded in established health care structures and points to health care-related barriers they face.Methods: We conducted 20 indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 47 publications
(61 reference statements)
0
15
0
Order By: Relevance
“…They reported that one of the main reasons why they were dissatisfied with their current health care provider was because they did not consider their birth history. 10 In our study, more than two-thirds (69%) of young adults born preterm who consulted a healthcare professional disclosed their birth status without being asked. This raises the question of selfadvocacy: Whether encouraging people to disclose their birth status during healthcare consultations could be part of knowledge transfer strategies for managing long-term health following preterm birth.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…They reported that one of the main reasons why they were dissatisfied with their current health care provider was because they did not consider their birth history. 10 In our study, more than two-thirds (69%) of young adults born preterm who consulted a healthcare professional disclosed their birth status without being asked. This raises the question of selfadvocacy: Whether encouraging people to disclose their birth status during healthcare consultations could be part of knowledge transfer strategies for managing long-term health following preterm birth.…”
Section: Discussionmentioning
confidence: 65%
“…6,7 However, data about the perspectives of adults born preterm, regarding their health status, healthcare needs and use, are limited. [8][9][10] Such information is key to planning effective knowledge transfer strategies to increase awareness and optimal care for adults born preterm. The goal of this study was to examine how adults born very preterm perceived their health, their healthcare needs and healthcare use compared with the general population.…”
mentioning
confidence: 99%
“…Parent-led organisations have started advocating for greater recognition of and research into the ongoing impact of preterm birth (Marlow et al, 2020;Ogilvy et al, 2017). Adults born preterm report that health professionals beyond those involved in early-life care are often unaware of their health needs, highlighting the need for better education on preterm birth for health professionals working with adolescents and adults (Perez et al, 2020). Considerably more work is needed to identify fruitful interventions or support strategies to ensure that preterm-born children achieve their potential.…”
Section: Psychosocial Development Across the Lifespan And Preterm Birthmentioning
confidence: 99%
“…Stories like Camille's are not uncommon. 1,2 Being born preterm Recent research demonstrates an elevated risk of chronic conditions such as hypertension, diabetes or airway obstruction 3 in young adults born preterm, which are generally asymptomatic at a young age. Children born preterm are also known to report more internalising problems such as anxiety and depression, which may result in an increased vulnerability for mental disorders in adulthood.…”
Section: Prematurit Y Is a Uni Que Conditionmentioning
confidence: 99%
“…Stories like Camille's are not uncommon 1,2 . Being born preterm is not a condition one can cure, like other illnesses.…”
Section: Prematurity Is a Unique Conditionmentioning
confidence: 99%